Hemostatic Antimicrobial Hydrogels Based on Silicon, Iron, Zinc, and Boron Glycerolates for Wound Healing Applications - Tat’yana Khonina; Semyon Alekseenko; Elena Shadrina; Il’ya Ganebnykh; Alexander Mekhaev; Leonid Larionov; Maria Dobrinskaya; Nadezhda Izmozherova; Irina Antropova; Maxim Karabanalov; Muza Kokhan; Natali’ya Evstigneeva; et al. (Gels)
The use of glycerolates of biogenic elements as biocompatible precursors in sol–gel synthesis is an innovative direction and opens up new scientific and practical prospects in chemistry and technology of producing practically important biomedical materials, including hemostatic, antimicrobial, and wound healing materials. Using biocompatible precursors, silicon, zinc, boron, and iron glycerolates, new bioactive nanocomposite hydrogels were obtained by the sol–gel method. The composition and structural features of the hydrogels were studied using a complex of modern analytical techniques, including TEM, XRD, AES, and ESI MS. Hemostatic activity of the hydrogels was studied in the in vivo experiments; using the example of silicon-iron-zinc-boron glycerolates hydrogel, primary toxicological studies were carried out. Antimicrobial properties of hydrogels were studied using the agar diffusion method. The structural features of hydrogels and their relationship to medical and biological properties were revealed. It was shown that glycerolates hydrogels are non-toxic, and exhibit pronounced hemostatic activity, generally comparable to the commercial hemostatic drug Capramine. Antimicrobial activity is more pronounced for silicon-iron-zinc-boron and silicon-iron-boron glycerolates gel. The results obtained indicate that these glycerolates hydrogels are potential hemostatic and antibiotic-independent antimicrobial agents for topical wound healing applications in medical and veterinary practice.